Identification and Role of Muscarinic Receptor Subtypes Expressed in Rat Adrenal Medullary Cells - Keita Harada; Hidetada Matsuoka; Takeyoshi Sata; Akira Warashina; Masumi Inoue (Elsevier, 2011)
Abstract.: The muscarinic receptor is known to be involved in the acetylcholine (ACh)-induced secretion of catecholamines in the adrenal medullary (AM) cells of various mammals. The muscarinic receptor subtype involved and its physiological role, however, have not been elucidated yet. Thus, we investigated these issues in acutely isolated rat AM cells and perfused rat adrenal medulla. The RT-PCR analysis revealed the presence of M2, M3, M4, and M5 mRNAs. Immunocytochemistry with specific antibodies showed that M5-like immunoreactivities (IRs) were detected at half the cell membrane area, which was much larger than that with M3- or M4-like IRs. Muscarine produced inward currents in a dose-dependent manner. Pilocarpine, McN-A-343, and oxotremorine were less efficient than muscarine; and RS-86, which has no action on the M5 receptor, produced no current. Electrical stimulation of nerve fibers produced a frequency-dependent increase in the Ca2+ signal in perfused adrenal medullae. Muscarinic receptors were found to be involved in neuronal transmission in AM cells in the presence of a cholinesterase inhibitor, which suppresses ACh degradation. We concluded that the M5 receptor is the major muscarinic receptor subtype in rat AM cells and may be involved in neuronal transmission under conditions where ACh spills over the synapse. Keywords:: muscarinic receptor, adrenal medulla, transmission, Ca imaging, TASK channel